Ecologia ecossistêmica de florestas tropicais: aplicações na restauração e proteção florestal - Maure, Lucas Andrigo (Universidade Federal de São Carlos, 2022)
Forest protection and restoration have been singled out as major solutions to stem the biggest environmental crises of our time: the loss of biodiversity and climate change. However, deciding which sites are appropriate and priority for protection and restoration is not an easy task. Thus, this thesis proposes an ecosystem approach to substantiate such decisions in the Brazilian Atlantic Forest. In the first chapter, we tested the effect of environmental predictors on the resilience and stability of early second-growth forests. Thus, we predict the spatial distribution of both ecosystem parameters to locate areas with ecosystem potential for forest restoration. In the second chapter, we test the effect of environmental predictors on the stability of old-growth forests. By predicting their distribution, we aim to find priority areas for forest protection and management with a focus on conservation of large numbers of species and carbon density. In the third chapter, we test the effect of climate on the stability of old-growth forests. By predicting their distribution based on current and future climate, we locate areas of gain and loss of forest stability as a result of climate change. While areas of gain have great potential, areas of loss of stability are a priority for forest protection and restoration aiming at the future conservation of species and carbon stocks. The results of this thesis shed light on decisions related to conservation of species and carbon stocks through an ecosystem view of their habitats.
Ecosystem ecology of tropical forests: applications on forest restoration and protection
Keywords: Restauração florestal; Áreas de proteção; Conservação da biodiversidade; Mudanças climáticas; Florestas tropicais; Mata Atlântica; Forest restoration; Protected areas; Biodiversity conservation; Tropical forests; Atlantic Forest; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::HIDROLOGIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS